Comprehensive Orthodontic Treatment of Adult Patient with Cleft Lip and Palate - Noemí Leiva Villagra; Miguel Muñoz Domon; Sebastian Véliz Méndez (Hindawi Limited, 2014)
The aim of the paper is to present full orthodontic treatment of an operated cleft lip adult patient. Case Report. An 18-year-old patient consulted for severe crowded teeth. He comes from a poor family. At that time he already had four operations (velum, palate, lip, and myringotomy). Treatment included maxillary expansion, tooth extraction, and fixed orthodontic, as well as kinesiology and speech therapy treatment. A multidisciplinary approach allowed us to achieve successfully an excellent result for this patient and gave him a harmonic smile and an optimal function without orthognathic surgery. Two years after treatment, occlusion remains stable.